iFuse - A Controllable Overcurrent Protection Device for Multi-Inverter Microgrids with High IBR Penetration - Agarwal, Kartavya; Benzaquen, Joseph; Divan, Deepak (Conference proceedings - IEEE Applied Power Electronics Conference and Exposition, 2023)
This paper presents a low-cost intelligent fuse (iFuse) concept that provides controllable overcurrent protection for systems with high inverter-based-resource (IBR) penetration that can experience wide fault current variability. The iFuse uses power electronics, sensing, and communications and integrates these elements with a traditional fuse. In detail, the proposed iFuse uses a rapid-melting passive fuse element to trip under the presence of high-fault currents, whereas its semiconductor-based actuation mechanism allows for controlled triggering below the fusing current of the fuse element. As a result, the iFuse can interrupt currents as low as 20% of the rated circuit current up to the desired interruption current. Moreover, local intelligence allows the iFuse to trip selectively and only when the downstream device is faulted. In this paper, the operation principles of the iFuse are articulated, and its controllability is demonstrated using numerical simulations. Lastly, to validate the survivability of the semiconductors in the iFuse under high levels of fault currents while the passive fuse-link trips, a laboratory-scale current pulse generation experimental testbed is developed to subject the devices under test to a 1.5-kA pulse.